Radiographic study of dental anomalies in brazilian patients with neuropsychomotor disorders - Erick Nelo Pedreira; Marina Cury Gallotini Magalhães; Camila Lopes Cardoso; Luís Antônio de Assis Taveira; Cláudio Froes de Freitas (University of São Paulo, 2007)
The purposes of this study were to investigate radiographically the dental and maxillomandibular in patients with neuropsychomotor disorders and determine the role of panoramic radiographs for quantitative and qualitative analyses of dental alterations. A total of 322 panoramic radiographs from 190 males and 132 females aged 4 to 57 years were obtained from the files of the Center for Care to Patients with Special Needs (CAPE; Dental School, University of São Paulo) and subdivided into syndromes, special needs, neurological, neuromuscular or cerebral disorders, and sequels of diseases. 32% of dental alterations were in tooth position, with 69% of this group associated with tooth rotation. The mandible accounted for 54.62% of alterations. The male gender (55.85%) and the permanent dentition (78.7%) were most affected. Panoramic radiographs were proved to be well suited for quantitative evaluation of dental anomalies of epidemiological nature. Panoramic radiographs are important diagnostic resources when applied to patients with special needs because of the difficulty to place intraoral films and held them correctly positioned during the radiographic technique.